Լուսեղեն երկրի առասպելը. Վահան Տերյան - Աիդա Մարտիրոսյան (ՀՀ ԳԱԱ հրատ.)
Мистику в лирике Терьяна следует рассматривать как отдельную тему, наивысшее восприятие и качество его поэтической эстетики, исключительное выражение его духовного света и миропонимания. It is a necessity to consider mysticism in Teryan's lyric poetry as a separate theme, as the highest perception and caliber of Ms poetic aesthetics, the absolute expression of Ms spiritual illumination and world-vision.
Keywords: Language and Literature